Neighbourhood unemployment and all cause mortality: a comparison of six countries. Issue 3 (11th February 2005) - van Lenthe, F J; Borrell, L N; Costa, G; Diez Roux, A V; Kauppinen, T M; Marinacci, C; Martikainen, P; Regidor, E; Stafford, M; Valkonen, T
Abstract : Study objective: Studies have shown that living in more deprived neighbourhoods is related to higher mortality rates, independent of individual socioeconomic characteristics. One approach that contributes to understanding the processes underlying this association is to examine whether the relation is modified by the country context. In this study, the size of the association between neighbourhood unemployment rates and all cause mortality was compared across samples from six countries (United States, Netherlands, England, Finland, Italy, and Spain). Design: Data from three prospective cohort studies (ARIC (US), GLOBE (Netherlands), and Whitehall II (England)) and three population based register studies (Helsinki, Turin, Madrid) were analysed. In each study, neighbourhood unemployment rates were derived from census, register based data. Cox proportional hazard models, taking into account the possible correlation of outcomes among people of the same neighbourhood, were used to assess the associations between neighbourhood unemployment and all cause mortality, adjusted for education and occupation at the individual level. Results: In men, after adjustment for age, education, and occupation, living in the quartile of neighbourhoods with the highest compared with the lowest unemployment rates was associated with increased hazards of mortality (14%–46%), although for the Whitehall II study associations were not statistically significant. Similar patterns were found in women, but associations were not statistically significant in two of the five studies that included women. Conclusions: Living in more deprived neighbourhoods is associated with increased all cause mortality in the US and five European countries, independent of individual socioeconomic characteristics. There is no evidence that country substantially modified this association.